(untitled) (Sinología hispánica. China Studies Review, 2016)
The fundamental objective of advertising discourse is to persuade target audiences to accept and purchase the advertised product, thus in essence, persuasiveness is crucial characteristic of advertising discourse. Actually, successful persuasion usually involves argumentativeness. Drawing on the research framework of Pragma-Dialectics, this paper attempts to explore a pragma-dialectical approach to advertisement discourse on the basis of the ideal model of critical discussion. This approach involves two interrelated parts: argumentative reconstruction and strategic maneuvering analysis. Taking the case of Melatonin advertisements, the pragma-dialectical approach can show the argumentativeness of advertisement discourse to a great extent and meanwhile reveals advertisers’ manipulation of dialectical reasonableness and rhetorical effectiveness. Therefore, the pragma-dialectical approach can not only give a deep insight into persuasiveness and argumentativeness of advertising discourse, but also provides a theoretical guidance for advertisers to skilfully employ dialectical strategies in advertising discourse. Consequently, such approach can offer a new perspective for comprehensive and systematic study of advertisement discourse.